Feminist pedagogy for library instruction - Accardi, Maria T. (Sacremento : Library Juice Press, 2013)
"Introduces feminist pedagogy to librarians seeking to enrich their teaching practices"--
Includes bibliographical references (pages 95-106) and index.
Keywords: Library orientation for college students; Information literacy -- Study and teaching (Higher); Research -- Methodology -- Study and teaching (Higher); Feminism and higher education; Critical pedagogy; Feminist theory